2019
DOI: 10.1016/j.pedneo.2019.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of group B streptococcal infection in pregnant women and diseased infants in mainland China

Abstract: Group B Streptococcus (GBS) is a leading cause of neonatal sepsis and an important cause of maternal disease in many countries; however, no accurate population-based epidemiological data on GBS is yet available in mainland China. In this systematic literature review, we obtained published data regarding the maternal GBS colonization rate, incidence of invasive GBS disease in infants, clinical screening, and the associated GBS typing and clinical outcomes in China. The maternal GBS colonization rate in mainland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 29 publications
3
26
1
Order By: Relevance
“…GBS is the leading cause of neonatal bacterial infection during gestation and after delivery, with significant mortality rates in premature infants (3). In China, several studies have reported 0.55-1.79 cases of GBS-EOD per 1,000 live births and severe GBS infection cases (4,5). Vaginal GBS colonization in pregnant women is an important risk factor for neonatal GBS-EOD (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…GBS is the leading cause of neonatal bacterial infection during gestation and after delivery, with significant mortality rates in premature infants (3). In China, several studies have reported 0.55-1.79 cases of GBS-EOD per 1,000 live births and severe GBS infection cases (4,5). Vaginal GBS colonization in pregnant women is an important risk factor for neonatal GBS-EOD (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the reported prevalence of GBS for Africa is 22.4%, Southeast Asia is 11.1% and Taiwan is 23.7% [13][14] . Unfortunately, largescale multicenter epidemiological studies on maternal GBS colonization in mainland China are still rare [15] .…”
Section: Discussionmentioning
confidence: 99%
“…For example, the reported prevalence of 5 GBS for Africa is 22.4%, Southeast Asia is 11.1% and Taiwan is 23.7% [13][14] . Unfortunately, largescale multicenter epidemiological studies on maternal GBS colonization in mainland China are still rare [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Screening of pregnant women for GBS colonization during the third trimester, coupled with targeted intrapartum antibiotic prophylaxis (IAP) of colonized women during labor, has reduced the incidence of invasive GBS disease in industrialized countries [4] . GBS detection and identification has become more commonplace, due to the availability of polymerase chain reaction technology [5] . However, the traditional method of culture of GBS is still the gold standard.…”
mentioning
confidence: 99%